Recent geodynamic characteristics of the Southern Central coast and the relations with geological hazards - Thanh, Bui Nhi; Luong, Nguyen Van; Hung, Duong Quoc; Diep, Nguyen Van; Dong, Mai Duc (Vietnam Journal of Marine Science and Technology, 2019)
Recent geodynamic characteristics of the Southern Central coast are analyzed on the basis of vertical and horizontal displacement velocities along active fault zones. The horizontal displacement velocity varies in magnitude from this fault system to another fault system, from 0.11–0.3 mm/year on the strike-slip - normal faults to 0–0.058 mm/year on the strike-slip faults and normal faults. The subsidence velocity changes complicatedly, different from one fault to another fault, depending on the mechanism of faults. On the continental shelf, most of the values of high subsidence’s velocity are related to the normal and strike-slip faults. Subsidence activities make the sea level increase highly, the subsidence activity makes the sea level rise at structures that fall close to the shore, reach about 0.2–0.48 mm/year in late Pleistocene - Holocene. The increase of sea level directly affects the intensity of erosion, flood, salinity and land loss events in coastal lowlands. Slippage of the seabed, earthquakes, volcanoes are geological hazards directly related to the geodynamic regime of the Southern Central coast.